In silico and in vivo verification of the mechanism of formononetin in treating hepatocellular carcinoma - Guiping Ma; Xu Pang; Yun Ran; Wenlin Chen; Yichi Zhou; Xiaobin Li; Bowen Liu; Feng Li; Shiping Hu (Annals of Medicine, 2024)
Background Hepatocellular carcinoma (HCC) remains a significant global medical challenge. Formononetin, an isoflavone derived from Astragalus membranaceus, has been shown to have various regulatory effects on HCC. However, the exact molecular mechanism by which formononetin acts against HCC is still unclear.Purpose To elucidate the molecular mechanism of formononetin in treating HCC.Methods The potential targets of formononetin were retrieved from Swisstargets and SEA databases, while targets associated with HCC were sourced from GeneCards, NCBI and DisGeNET databases. The overlapping targets were visualized using protein–protein interaction (PPI) network analysis via String database, and subsequently subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. Molecular docking was employed to confirm the interaction between formononetin and key targets. Ultimately, the effectiveness of formononetin on HCC and the signalling pathway with the highest enrichment were confirmed in the HCC tumour-bearing mice. Histopathological changes in tumour tissues were observed using haematoxylin and eosin (HE) staining, while apoptosis of tumour cells in mice was assessed through TdT-mediated dUTP nick end labelling (TUNEL) and immunofluorescence staining. The most enriched signalling pathway was verified using Western blotting and immunohistochemical (IHC) staining.Results One hundred and ninety-three potential targets related to formononetin, 6980 targets associated with HCC and 156 overlapping targets were obtained from the online public databases. Molecular docking studies demonstrated formononetin’s robust interaction with core targets. KEGG enrichment analysis identified 111 signalling pathways, including PI3K/AKT and apoptosis signalling pathways. In vivo experiments demonstrated that formononetin significantly promoted apoptosis of tumour cell in mice, as confirmed by HE, TUNEL and immunofluorescence staining (p < .05). Formononetin was found to decrease the phosphorylation levels of PI3K and AKT, reduce the expression of Bcl-2, and increase the expression of cleaved-Caspase-3 and Bax (p < .05).Conclusions Formononetin demonstrates dose-dependent regulatory effects on multiple targets, biological processes and signalling pathways in HCC. The compound can mitigate HCC by enhancing PI3K/AKT-mediated apoptosis of tumour cells.